Analisis Resiko Kebangkrutan Pada Perusahaan Dengan Laporan Ekuitas Negatif - Antonius Yudhis Hindriarsana; Darti Djuharni (Syntax Idea)
The Altman, Springate, and Zmijewski methods were used in this study to analyze the comparison of bankruptcy risk calculations and analyze the influence of negative equity on bankruptcy risk quantitatively using a population of 810 companies listed on the Indonesian Stock Exchange. Then, a sample of 23 companies was selected using purposive sampling technique by applying several criteria. The research results indicate that the Altman, Springate, and Zmijewski methods provide different bankruptcy prediction results and levels of accuracy in predicting the tested companies. Among the three methods, the Altman method is the highest in predicting bankruptcy with 18 companies, compared to 16 companies for the Springate method and 8 companies for the Zmijewski method. Furthermore, based on the t-test results, it is found that the Altman and Springate methods show that companies with negative equity have a positive and significant impact on bankruptcy risk. However, the Zmijewski method yields different results, where companies with negative equity do not have a positive and significant influence on bankruptcy risk.